A finalidade do rito no espaço escolar: uma abordagem simbólica do primeiro dia de aula - Silva, Jailson da (2013)
The understanding of the importance of both rites and school for humanity, something so unique, sparked this investigative work. As a contribution, thinking about these considerations that rites accompany men in all stages of life and in school spaces which are places of learning, this research was structured referring to the purpose of the rite at school, bringing a symbolic approach of the first day of class. In this sense, the goal of this dissertation was to analyze the symbolic value of the initiation rite, in the context of Luiz Vaz de Camões School, in João Pessoa, Paraíba. In this case, the research was based on the observations of the first day of class of the students that change from elementary I into II. At first, it was highlighted the importance of school and learning acquired in this space, then it was stressed the importance of the rite for humans and thus to society, and eventually, school and rite were associated; assigning the symbolic value that initiation rite has for students on their first day of class. As a methodological tool, a literature search was done, so this study sought to be guided by the thought of some authors who work these issues: rite and school, such as Amado Luiz Cervo and Pedro Alcino Bervian, showing the importance of literature; Aldo Natale Terrin and Maria Ângela Vilhena, speaking of the importance of the rite; Carlos Rodrigues Brandão and Nelson Piletti, treating about education and school; Claude Lévi Strauss, Bronislaw Malinowski, along with Franz Boas, sharing about culture, José Maria Mardones, Mircea Eliade and Ernest Cassirer, talking about the symbols and symbolic ones, among others that supported this dissertation becoming their theoretical references.